Angiotensin-Converting Enzyme Inhibitors and Angiotensin II Receptor Blockers in Patients With Abdominal Aortic Aneurysms: Nation-Wide Cohort Study - Kristensen, Karl Emil; Torp-Pedersen, Christian; Gislason, Gunnar Hilmar; Egfjord, Martin; Rasmussen, Henrik Berg; Hansen, Peter Riis (Arteriosclerosis, thrombosis, and vascular biology, 2015)
OBJECTIVE—The renin–angiotensin system is thought to play a pivotal role in the pathogenesis of abdominal aortic aneurysms (AAAs). However, effects of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II type 1 receptor blockers (ARBs) on human AAAs remain unclear. We therefore examined whether treatment with ACEIs or ARBs influenced hard clinical end points in a nation-wide cohort of patients with AAA. APPROACH AND RESULTS—All patients diagnosed with AAA during the period 1995 to 2011 were identified from the Danish nation-wide registries. Subjects were divided according to ACEI and ARB treatment status and followed up for an average of 5 years. Study outcomes were evaluated by time-dependent Cox proportional hazard models. Of 9441 patients with AAA, 12.6% were treated with ACEIs and 5.0% received ARBs. Incidence rates of death from AAA per 100 patient-years were 3.7, 3.6, 4.0, and 4.7 for treatment with ACEIs or ARBs, ACEIs, ARBs, and no ACEI/ARB, respectively. Hazard ratios of death from AAA were 0.64 (95% confidence interval, 0.51–0.80; P<0.001) for patients receiving ACEIs and 0.65 (95% confidence interval, 0.48–0.88; P=0.006) for those receiving ARBs, respectively (P for difference=0.944). The risk of surgery for AAA was significantly reduced in patients receiving ACEIs (hazard ratio, 0.86 [95% confidence interval, 0.74–0.99]; P=0.040) but not in patients receiving ARBs (hazard ratio, 1.02 [95% confidence interval, 0.84–1.23]; P=0.867; P for difference=0.119). CONCLUSIONS—In this observational study, treatment with ACEIs or ARBs was associated with a comparable reduction in mortality but not in surgery for AAA among patients with AAA. Randomized controlled trials are warranted to confirm these findings.